AAAP gene family evolution and transcriptional regulation in Eucalyptus grandis under nitrogen, phosphate and boron deficiencies - Jiahui Wei; Yi Han; Huiming Xu; Lichuan Deng; Lu Li; Shasha Zhang; Ting Jiang; Yunzhuo Feng; Liuyin Ma (BMC Plant Biology)
Abstract Background Eucalyptus is one of the most important fast-growing tree species in the world, and its growth and development are significantly affected by nitrogen and phosphorus. The Amino acid/auxin permease (AAAP) gene family plays key roles in long-distance amino acid transport in plants, but their evolutionary diversity and gene expression analysis in Eucalyptus grandis under nutrient deficiency stress are largely unexplored. Results This study presents the first genome-wide identification and functional characterization of 78 AAAP family genes (EgAAAPs) in Eucalyptus grandis, classified into eight subfamilies. Phylogenetic analysis of 28 species across five evolutionary stages revealed the AAAP family’s classification into three groups: Group III originating from green algae and Groups I-II from mosses. This study underscores lineage-specific expansions (e.g., Eucalyptus AAPs) and algal ancestors as pivotal drivers of functional diversification during early land plant adaptation. Structural analysis revealed subfamily-specific features, including conserved motifs, domain variations, and exon-intron heterogeneity, underpinning functional divergence. Tandem duplication dominated EgAAAP expansion, with syntenic conservation to Populus trichocarpa offering molecular insights into Myrtaceae-Salicaceae divergence. Transcriptional regulatory networks identified 166 transcription factors (MYBs, WRKYs, NACs), with subgroup-specific cis-element enrichment: WRKY binding in Group II and RGA-LIKE1 in Groups I/III, mechanistically linking phosphate/nitrogen signaling. Cross-species interaction hubs of key EgAAAPs (e.g., EgAAAP37, EgAAAP38, EgAAAP41, EgAAAP42, EgAAAP43 and EgAAAP78) with stress-responsive proteins (ABCG40, STP1), amino acid transporters (UMAMITs, CAT5/6), and metal carriers (YSLs) revealed woody plant-specific networks absent in Arabidopsis. Spatiotemporal expression profiling delineated six tissue-specific clusters and dynamic hormonal responses: SA/JA induced temporally distinct modules (early, sustained, delayed), while boron/nitrogen/phosphorus deficiency triggered subgroup- and tissue-dependent regulation. Conclusions Collectively, this study deciphers the evolutionary innovation, regulatory complexity, and functional specialization of AAAP transporters in Eucalyptus, providing a framework for understanding nutrient signaling and stress resilience in woody plants.